A HEURISTIC APPROACH FOR INDEX TRACKING PROBLEM: A CASE STUDY OF TEHRAN EXCHANGE PRICE INDEX - Mohsen Varsei,; Naser Shams,; Behnam Fahimnia,; Abbas Yazdanpanah, (Asian Academy of Management Journal, 2013)
Index tracking problem, the most popular form of passive fund management, is a portfolio selection problem in which the return of one of the stock market indexes is reproduced by creating a tracking portfolio consisting of a subset of the stocks included in the index. Index tracking has been known as a NP-Hard problem and sophisticated solution approaches have been proposed in the literature to solve this problem. This paper presents an easy-to-implement heuristic solution to tackle this complex problem. The proposed approach is implemented to develop a tracking portfolio from 438 stocks listed in Tehran Exchange Price Index. The numerical results indicate that the approach is able to find quality solutions within reasonable model runtime.